1999
DOI: 10.1590/s0001-37141999000100005
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of meningoencephalitis in rabbits by bovine herpesvirus type-5 (BHV-5)

Abstract: This article describes the main aspects of bovine herpesvirus type-5 (BHV-5) neurologic infection and disease in rabbits, a candidate animal model for studying BHV-5 neuropathogenesis. Intranasal inoculation of weanling rabbits with a Brazilian BHV-5 isolate produced neurological disease and death in 78.8% (26/33) of the animals. Neurological signs started as early as 5 days post-inoculation and lasted from 10-12 hours up to several days. Most animals evolved to a moribund state or death within 24 (69.2%) to 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
24

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 28 publications
1
9
0
24
Order By: Relevance
“…We believe that differences in age and breed of the infected rabbits could not justify such discrepancies, since these were comparable in both experiments. On the other hand, differences between virus strains might be a relevant source of variation, since it has been shown that different BoHV-5 isolates may significantly differ in their neurovirulence (Silva et al 1999, Beltrão et al 2001. When inoculated in older animals, the recombinant virus was apathogenic, contrasting with the effect of the wild type virus infection (which caused death in 55.5 % of infected animals).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that differences in age and breed of the infected rabbits could not justify such discrepancies, since these were comparable in both experiments. On the other hand, differences between virus strains might be a relevant source of variation, since it has been shown that different BoHV-5 isolates may significantly differ in their neurovirulence (Silva et al 1999, Beltrão et al 2001. When inoculated in older animals, the recombinant virus was apathogenic, contrasting with the effect of the wild type virus infection (which caused death in 55.5 % of infected animals).…”
Section: Discussionmentioning
confidence: 99%
“…Before infection rabbits were anesthesized with 2 mg of tiletamine/zolazepam (Zoletil, Virbac) and inoculated into each paranasal sinuses with a total volume of 0.5mL as described previously (Brown & Field. 1990, Silva et al 1999). …”
Section: Design Of the Animal Experimentsmentioning
confidence: 99%
“…Os animais dos Grupos 1 e 2 foram inoculados pela via intranasal (IN), através de aberturas dorso-laterais dos seios paranasais (protocolo adaptado por Silva et al 1999). Para tal, os animais foram previamente anestesiados com 2mg de Tiletamina/Zolazepam (Zoletil, Virbac).…”
Section: Células E Vírus Células E Vírus Células E Vírus Células E Víunclassified
“…Em particular, os coelhos têm sido amplamente utilizados para estudar vários aspectos da neuropatogenia da infecção pelo BoHV-5, pois desenvolvem infecção e doença neurológica com certas similaridades àquela observada em bovinos (Meyer et al 1996, Chowdhury et al 1997, Silva et al 1999b.…”
Section: Introductionunclassified
“…Os primeiros estudos nesta espécie foram realizados para caracterizar os aspectos virológicos, clíni-cos e patológicos da infecção neurológica aguda, e avaliar a adequação desta espécie como modelo experimental para esse vírus (Silva et al 1999b). A partir desses estudos, vários aspectos relacionados com a patogenia, imunidade e terapia antiviral foram abordados (Beltrão et al 2000, Spilki et al 2000, Diel et al 2005, Dezengrini et al 2008a.…”
Section: Introductionunclassified